Influence of Chinese cultural values on consumer decision-making: a PRISMA-based systematic review - Wang, Na; Zainal Abidin, Sazrinee; Shaari, Nazlina (Institute of Advanced Science Extension (IASE), 2024)
Employing the preferred reporting items for systematic reviews and metaanalyses (PRISMA) methodology, this study provides an incisive exploration into the nexus between traditional Chinese cultural values and their impact on consumer decision-making processes. The central objective was to ascertain the degree to which these ingrained cultural values shape purchasing behaviors. Our systematic review discerns a pronounced effect of these cultural tenets on consumer choices within the Chinese market. It reveals that the purchasing decisions of Chinese consumers are inextricably linked to specific cultural value orientations. For enterprises seeking to penetrate or thrive in this market, a nuanced comprehension of these cultural dimensions is imperative for crafting successful marketing strategies and customer engagement approaches. The findings of this research are instrumental in offering crucial insights for aligning business strategies with the unique preferences and behavioral patterns of Chinese consumers.